The emerging applications and advancements of Raman spectroscopy in pediatric cancers - Li, Chenbei; Feng, Chengyao; Xu, Ruiling; Jiang, Buchan; Li, Lan; He, Yu; Tu, Chao; Li, Zhihong (Frontiers in Oncology, 2023)
Although the survival rate of pediatric cancers is significantly improved in recent years, it is still a crucial cause of children’s death. In order to achieve higher chance of survival, novel technologies have been developed to improve the diagnosis, treatment as well as prognosis of pediatric cancers. Raman spectroscopy (RS) is a non-destructive analytical technique using different frequency of scattering light to characterize the biological specimen. It can provide information of biological components, activities, and molecular structures. Differences between normal and cancerous samples could be revealed by RS. In this review, we summarized recent studies regarding the potential application of RS in benefiting diagnosis and improving treatment in pediatric cancers. The current situation, limitations, and future perspectives of RS and its derivates application were also discussed.